Innovation in the South Bahia Coast Public Management: Analysis of the Agir-Ls Extension Program of the Universidade Estadual de Santa Cruz (Research, Society and Development, 2020)
This study aims to analyze the innovation potential of the Extension Program AGIR-LS (Programa de Apoio Gerencial e Institucional às Prefeituras da Região Litoral Sul da Bahia), coordinated by the Universidade Estadual de Santa Cruz through the Extension Pro-rectory in a partnership with AMURC (Associação dos Municípios do Sul, Extremo-Sul e Sudoeste da Bahia). The parameters used for this analysis were the eight evaluation criteria used by the 22nd Innovation Competition in the Federal Public Management of Escola Nacional de Administração (ENAP). In the quantitative evaluation of the Program, an individual score was given per criterion and multiplied by its weight at the formula created for this study and a qualitative evaluation was also elaborated according to the concepts of innovation in Public Management addressed throughout it. As main results it was possible to point out that the AGIR-LS Program has the potential of innovation through meeting the criteria required by ENAP, reaching final grade 8,27; and framing the qualitative concepts of innovation in public management worked on in the article. This study becomes an important source of consultation on the AGIR-LS Program mainly, considering the Replicability factor, in which cities can adopt the same format of action as a propulsor of changes in local and regional public management.